2010
DOI: 10.1111/j.1365-2672.2010.04891.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad-range antagonistic rhizobacteria Pseudomonas fluorescens and Serratia plymuthica suppress Agrobacterium crown gall tumours on tomato plants

Abstract: Aim: To examine the biocontrol activity of broad-range antagonists Serratia plymuthica IC1270, Pseudomonas fluorescens Q8r1-96 and P. fluorescens B-4117 against tumourigenic strains of Agrobacterium tumefaciens and A. vitis. Methods and Results: Under greenhouse conditions, the antagonists, applied via root soak prior to injecting Agrobacterium strains into the wounded stems, significantly suppressed tumour development on tomato seedlings. A derivative of P. fluorescens Q8r1-96 tagged with a gfp reporter, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 32 publications
7
122
0
1
Order By: Relevance
“…In a meta-analysis of 31 studies on volatiles emitted by six common pathogenic bacteria, 1-undecene was one of the molecules that differentiated Pseudomonas aeruginosa from the other, non-Pseudomonas pathogenic bacteria (32). Within the genus Pseudomonas, it seems that the relative contribution of undecene to the volatile bouquet of the strains is highly variable, ranging from the unchallenged dominance observed in our rhizosphere strains or in other antagonistic P. fluorescens strains (33) to the absence of detection for some strains, such as P. syringae S22 and P. jessenii S34. Other studies have reported 1-undecene from the headspace of Pseudomonas strains (7,(34)(35)(36) but also from other species, including members of the genera Burkholderia, Bacillus, and Serratia (7, 37).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 31 studies on volatiles emitted by six common pathogenic bacteria, 1-undecene was one of the molecules that differentiated Pseudomonas aeruginosa from the other, non-Pseudomonas pathogenic bacteria (32). Within the genus Pseudomonas, it seems that the relative contribution of undecene to the volatile bouquet of the strains is highly variable, ranging from the unchallenged dominance observed in our rhizosphere strains or in other antagonistic P. fluorescens strains (33) to the absence of detection for some strains, such as P. syringae S22 and P. jessenii S34. Other studies have reported 1-undecene from the headspace of Pseudomonas strains (7,(34)(35)(36) but also from other species, including members of the genera Burkholderia, Bacillus, and Serratia (7, 37).…”
Section: Discussionmentioning
confidence: 99%
“…DMDS was first described as produced by bacteria isolated from decomposing chicken (Freeman et al, 1976). Surprisingly, DMDS, along with other VOCs emitted by rhizobacteria Pseudomonas fluorescens B-4117 and Serratia plymuthica IC1270, was found to exert antimicrobial and nematicidal activity Wang et al, 2009;Huang et al, 2010;Dandurishvili et al, 2011) and to inhibit the cell-cell communication quorumsensing network of various bacteria . Furthermore, DMDS functions as a plant defense compound against nonspecialist herbivores feeding on Allium porrum (Dugravot et al, 2003(Dugravot et al, , 2004 and as both an oviposition repellent and an attractant to different natural enemies of the cabbage root fly Delia radicum (Ferry et al, 2007(Ferry et al, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dandurishvili et al (2011) reported that volatiles emitted by Pseudomonas fluorescens and Serratia plymuthica have bacteriostatic effects against the bacterial plant pathogens Agrobacterium tumefaciens and A. vitis and inhibited the growth of these pathogens in planta. The major volatile emitted by S. plymuthica under the tested conditions was dimethyl disulphide, whereas P. fluorescens emitted a mix of 1-undecene, methanthiol, methanthiol acetate and dimethyl disulphide (Dandurishvili et al, 2011).…”
Section: Volatile-mediated Antibacterial Activitymentioning
confidence: 99%